Does ECB communication help in predicting its interest rate decisions? - David-Jan Jansen; Jakob de Haan; Christoph A. Schaltegger (Center for Economic Studies and ifo Institute (CESifo), 2006)
We examine the usefulness of communication by the European Central Bank for predicting its interest rate decisions. We use ordered probit models based on the Taylor rule which we estimate using statements by ECB officials as well as macroeconomic variables. Statements by ECB officials on the main refinancing rate and future inflation are significantly related to ECB decisions. However, an out-of-sample evaluation shows that communication-based models do not outperform models based on macroeconomic data in predicting decisions. Both sets of models only accurately predict decisions to leave interest rates unchanged.
Keywords: E43; E52; E58; 330